Evaluation of the effectiveness of combined podiatric therapy using essential oils in the topical treatment of toenail onychomycosis - Kuros, Faustyna; Wcisło-Dziadecka, Dominika L. (Medical Studies/Studia Medyczne, 2026)
Introduction: Mycotic infections are difficult to treat and often require long-term therapeutic regimens. Many authors believe that topical therapy is at the forefront of nail disease treatment because of fewer side effects than combined therapy. Aim of the research: The present study evaluated the efficacy of podiatric therapy using a blend of essential oils for the treatment of toenail onychomycosis and the quality of life of patients. Material and methods: A randomised evaluation of the effectiveness of therapy on 40 patients with onychomycosis confirmed by mycological examination was conducted in a podiatry office. The participants were randomly assigned to groups I (experimental) and II (control). After cleaning the pathologically affected fragments of the nail plate, the patients in group I received topical serum with essential oils twice a day. Results: A significant difference was observed in the effectiveness of the therapy after 5–6 months. Healthy nail growth was observed in 45.0% (n = 9) of Group I patients after 3–4 months of essential oil therapy. In Group II, the corresponding proportions increased over time but were lower than those in Group I at each follow-up visit (20.0%, n = 4). Quality of life scores increased from 2.00 to 5.50 (median) on a scale of 1 to 7 in Group I, and from 2.20 ±0.95 to 4.00 ±1.30 on a scale of 1 to 7 in Group II, respectively. Podiatric therapy improved nail appearance. Conclusions: The use of essential oil-based serum in combination with nail milling constitutes a suitable topical treatment strategy and can be a safe additional therapy.